2008
DOI: 10.1152/ajplung.00503.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain of alveolar type II cells in culture: changes in the transcellular cytokeratin network and adaptations

Abstract: Mechanical forces exert multiple effects in cells, ranging from altered protein expression patterns to cell damage and death. Despite undisputable biological importance, little is known about structural changes in cells subjected to strain ex vivo. Here, we undertake the first transmission electron microscopy investigation combined with fluorescence imaging on pulmonary alveolar type II cells that are subjected to equibiaxial strain. When cells are investigated immediately after stretch, we demonstrate that cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 40 publications
(36 reference statements)
4
29
0
Order By: Relevance
“…Indeed, Gajic et al found signs of reversible cell membrane stress failure in rats ventilated with high tidal volumes using propidium iodide as a cell-impermeable marker of cell damage [72]. In addition, we found ultrastructural evidence for membrane damage in type II pneumocytes stretched on silastic membranes [71]. In summary, in pathophysiological conditions, ATP leakage from wounded cells could influence type II cells and surfactant secretion in an autocrine/paracrine way.…”
Section: Possible Causes Of Atp Release In the Alveolussupporting
confidence: 60%
See 1 more Smart Citation
“…Indeed, Gajic et al found signs of reversible cell membrane stress failure in rats ventilated with high tidal volumes using propidium iodide as a cell-impermeable marker of cell damage [72]. In addition, we found ultrastructural evidence for membrane damage in type II pneumocytes stretched on silastic membranes [71]. In summary, in pathophysiological conditions, ATP leakage from wounded cells could influence type II cells and surfactant secretion in an autocrine/paracrine way.…”
Section: Possible Causes Of Atp Release In the Alveolussupporting
confidence: 60%
“…However, although various anion channels have been identified in fetal and adult pneumocytes [70], their involvement in alveolar ATP release has not yet been demonstrated. It is unlikely that membrane stress alone is the reason for ATP release from cells under physiological conditions, because moderate amounts of stretch are in general tolerated without signs of membrane damage [35,36,71,72]. However, ATP may exit all cells under conditions of cell damage, and this could be the case in hyperinflation-induced lung injury.…”
Section: Possible Causes Of Atp Release In the Alveolusmentioning
confidence: 99%
“…In the liver, K8/K18 levels increase about threefold (mRNA and protein) in response to injury, as noted in mice treated with agents that induce Mallory–Denk body formation (Zatloukal et al , 2007) and in the hepatoma cell line HepG2 treated with doxorubicin (Wang et al , 2009; Hammer et al , 2010), and two- to fourfold (protein) in patients with primary biliary cirrhosis (Fickert et al , 2003). In alveolar epithelial cells, shear stress causes structural remodeling of the keratin IF network (Felder et al , 2008; Sivaramakrishnan et al , 2008), whereas hypoxia results in network disassembly and K8/K18 degradation (Na et al , 2010). Similarly, the keratin cytoskeleton disintegrates in mammary epithelial cells under metabolic (combined glucose and oxygen deprivation mimicking the tumor microenvironment; Nelson et al , 2004) stress (Kongara et al , 2010).…”
Section: Keratins In Healthmentioning
confidence: 99%
“…Post-translational modifications are major regulators of keratin function Ku et al, 1999;Toivola et al, 2004;Magin et al, 2007). In particular, serine phosphorylation of keratins plays a major role in various cellular events including apoptosis and mechanical or nonmechanical stress (Liao et al, 1995b;Liao et al, 1997;Ridge et al, 2005;Jeon et al, 2006;Felder et al, 2008). Serine hyperphosphorylation of keratins, for example by treatment of cells with okadaic acid, leads to disruption of the filament network (Ku and Omary, 1994;Ku et al, 1999;Strnad et al, 2002).…”
Section: Journal Of Cell Science 125 (9) 2154mentioning
confidence: 99%